Control failure of deltamethrin in Colombian populations of Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) - Ramírez-Cabrera, Carlos; López-Díaz , Gheraldin; Canal, Nelson A.; Bacca , Tito (Revista de Ciencias Agrícolas, 2024)
Rhyzopertha dominica (F.) is a major pest in stored cereals in Colombia, which causes significant losses in production. Chemical control is the main tool used in the country, and despite the common use of insecticides such as deltamethrin, resistance has been observed in some Colombian populations but is a worldwide problem. The objective of this work was to evaluate the efficacy of deltamethrin and the combination of deltamethrin and piperonyl butoxide in Colombian populations of R. dominica. Failure to control and survival tests showed that the recommended doses on product labels were insufficient to protect the grain from this pest. Failure control demonstrated that mortality did not exceed 80 percent in the populations studied. Differences in susceptibility were observed between populations, with El Espinal and Neiva highlighted as less susceptible and Pore as the most sensitive to the action of insecticides. The combination of deltamethrin and piperonyl butoxide reduced insect survival but did not effectively control it (0–20%). These results suggest that R. dominica may be developing resistance to insecticides, as has been found in other countries. This underscores the importance of conducting toxicological studies and the need to investigate molecules with diverse modes of action, contributing to the strengthening of chemical management strategies. To achieve effective control, it is necessary to implement Integrated Pest Management (IPM) with a focus on alternative methods to chemical control.